2005
DOI: 10.1086/429830
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection-Associated Smooth-Muscle Tumors in Patients with AIDS

Abstract: SMTs in patients with AIDS typically arise in multiple and very unusual sites that are not often observed in SMTs among immunocompetent individuals. Our series also suggests association between EBV infection and SMTs in patients with AIDS. The exact role of EBV in smooth-muscle oncogenesis awaits further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
143
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(151 citation statements)
references
References 32 publications
8
143
0
Order By: Relevance
“…Some studies have reported an association with HIV infection and the Epstein-Barr virus infection, and the possibility of a viral infection etiology has been suggested [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an association with HIV infection and the Epstein-Barr virus infection, and the possibility of a viral infection etiology has been suggested [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Iris leiomyosarcoma is an extremely rare malignant tumor [4][5][6]. It arises from the dilator and sphincter muscles, which are of neuroectoderm in origin.…”
Section: Commentmentioning
confidence: 99%
“…It arises from the dilator and sphincter muscles, which are of neuroectoderm in origin. Ebstein-Barr virus has been intimately associated, though not necessarily in a causal fashion, with multiple malignancies in AIDS including Burkitt's lymphoma, nasopharyngeal carcinoma, Hodgkin's disease, B-cell lymphomas [1], and leiomyosarcoma [4,5,7,8]. Although intraocular leiomyosarcoma has a potential to spread locally, it rarely metastasizes to distant organs resulting in an excellent survival prognosis [9].…”
Section: Commentmentioning
confidence: 99%
“…The most frequently reported EBV-associated malignancies are Burkitt lymphoma, Hodgkin lymphoma, post-transplant lymphoproliferative disorder (PTLD), and nasopharyngeal carcinoma (1)(2)(3)(4). Recently, the strong relation of EBV to the development of smooth muscle tumors (SMTs) in immunocompromised patients has been increasingly recognized, mainly in post-transplantation and AIDS patients (5,6). EBV-SMTs are rare neoplasms, with less than 30 cases reported in post solid organ transplantation pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…EBV-SMTs are rare neoplasms, with less than 30 cases reported in post solid organ transplantation pediatric patients. They are usually multicentric and exhibit a predilection to occur in sites that are unusual for conventional SMTs, most commonly the liver and lung (5,6).…”
Section: Introductionmentioning
confidence: 99%